The “two sessions”: institutional investors selloff to avoid ambiguity - Jiarui Wang; Haijun Yang; Shancun Liu (Financial Innovation)
Abstract We construct a model to examine the time-varying ambiguity of investors. When ambiguity occurs concerning recent news, long (short) position investors who are averse to ambiguity reduce (increase) their holdings, resulting in price drops (rises). We empirically analyze how the “two sessions,” a significant event with high policy ambiguity in China, affect the financial market. Our findings suggest that institutional investors mainly sell their holdings between 15 and 5 days before the meetings. Furthermore, the delay in the “two sessions” in 2020 suggests that these selloffs are driven by ambiguity aversion rather than new information.